Level of Awareness, Acceptance, and Congruency with the Vision, Mission, Goals, and Program Outcomes of the College of Education of Capiz State University (CAPSU) - Joaquin, Cleo Jude A.; BESA, Ellen Mae D.; Joaquin, Hazel D. (Future Science / FSH-PH Publications, 2023)
This research evaluated the level of awareness, acceptance, and congruence with the Vision, Mission, and Goals (VMGO) and Program Outcomes of the College of Education at Capiz State University (CAPSU). It adopted a mixed-method research design, utilizing a descriptive-quantitative approach, with both internal and external stakeholders of CAPSU as the primary data source. Through a survey questionnaire employing a five-point Likert scale, this study measures stakeholders' awareness, acceptability, and congruence with CapSU's VMG and the program outcomes of the College of Education. The gathered data were analyzed using weighted mean, T-test, and Pearson Correlation via SPSS software (version 20). Findings suggest a high level of awareness and acceptance of CAPSU’s VMGO among internal and external stakeholders, and a high congruence between the VMGO and actual educational practices. Interestingly, external stakeholders showed moderate acceptance of the College of Education's program outcomes. No significant difference was found between internal and external stakeholders' levels of awareness and acceptance, nor any correlation among these variables. The study concludes by highlighting the necessity for continuous efforts to enhance stakeholders' awareness, acceptance, and congruence with the VMGO and program outcomes. Additionally, it emphasizes the importance of stakeholder involvement in any revision process related to the VMGO. Lastly, the study recommends periodic assessments of stakeholders' awareness and acceptance of the VMG for sustainable institutional development.